2002
DOI: 10.1177/0011000002305007
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of European American Therapists’ Approach to Counseling African American Clients

Abstract: Interviews were conducted with 9 European American psychologists, asking them to recall their first 12 counseling sessions with a current or recent successful case with an African American client. Using consensual qualitative research (CQR) methodology, the psychologists revealed that they generally attended to differences in race between themselves and clients directly and openly within the first two sessions. This was done to acknowledge this difference and convey to the client comfort and trust; psychologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…This is consistent with the cultural competency literature that highlights the benefit of adding techniques to the existing model within which the therapist and BME client are working (Fuertes et al, 2002), in this case CBT. An additive approach is preferable to replacing techniques with supposedly culturally appropriate equivalents (Sue, Zane, Nagayama-Hall, & Berger, 2009).…”
Section: Implications Of Having An Ethnically Dissimilar Therapistsupporting
confidence: 86%
See 3 more Smart Citations
“…This is consistent with the cultural competency literature that highlights the benefit of adding techniques to the existing model within which the therapist and BME client are working (Fuertes et al, 2002), in this case CBT. An additive approach is preferable to replacing techniques with supposedly culturally appropriate equivalents (Sue, Zane, Nagayama-Hall, & Berger, 2009).…”
Section: Implications Of Having An Ethnically Dissimilar Therapistsupporting
confidence: 86%
“…Interestingly, this mirrors the concerns of therapists in addressing racial differences between client and therapist in adult psychotherapy settings (Fuertes et al, 2002;Maxie, Arnold, & Stephenson, 2006), again suggesting that therapists share the same concerns as clients. The participants suggested that asking questions at the wrong time (for instance the first session) would make the client feel uncomfortable and less likely to open up about their background and how it was important (or not) to them.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Findings indicate that therapists (Fuertes, Mueller, Chauhan, Walker, & Ladany, 2002) with a knowledge of racial-identity theory (Helms, 1990) and awareness of its central role in their clients' lives were able to make statements about their clients' racial identity. They also were able to describe their clients' interpersonal concerns as deeply intertwined with factors such as racism, homophobia, and poverty.…”
Section: Racismmentioning
confidence: 97%